It's all Mediating : Outlining and Incorporating the Roles of Curating and Education in the Exhibition Context. - Kokkonen, Laura (Cambridge Scholars Publishing, 2013)
It's all Mediating: Outlining and Incorporating the Roles of Curating and Education in the Exhibition Context brings together thinkers and practitioners in the fields of exhibition curating and gallery education from different corners of Europe. The publication explores the two core functions of museums: exhibiting of the content and educational activities directed to audiences. These areas of activity - both committed to ""mediating"" between art and its audience - have existed since the bir ...